2022
DOI: 10.3389/fonc.2022.905976
|View full text |Cite
|
Sign up to set email alerts
|

Meningioma Related Epilepsy- Pathophysiology, Pre/postoperative Seizures Predicators and Treatment

Abstract: Meningiomas are the most common primary brain tumors accounting for about 30% of all brain tumors. The vast majority of meningiomas are slow-growing and of benign histopathology rendering them curable by surgery alone. Symptomatic lesions depend on the location with signs of mass effect or neurological deficits. Seizures are the presenting symptoms in approximately 30% of cases, which negatively affect quality of life, limit independence, impair cognitive functioning, as well as increase the risk for psychiatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 67 publications
(184 reference statements)
1
48
0
Order By: Relevance
“…The mechanism underlying preoperative seizures in patients harboring meningiomas is a current topic of investigation. 32 We observed that a lower number of arterial feeders trended toward a positive association with the likelihood of seizure on presentation, controlling for tumor grade, size, and PTBE. This may be the corollary of studies in gliomas, showing that tumor hypoxia lowers peritumoral pH and seizure threshold.…”
Section: Discussionmentioning
confidence: 58%
“…The mechanism underlying preoperative seizures in patients harboring meningiomas is a current topic of investigation. 32 We observed that a lower number of arterial feeders trended toward a positive association with the likelihood of seizure on presentation, controlling for tumor grade, size, and PTBE. This may be the corollary of studies in gliomas, showing that tumor hypoxia lowers peritumoral pH and seizure threshold.…”
Section: Discussionmentioning
confidence: 58%
“…These figures quite often are results from studies carried out in the past, the results of which are still cited in recent articles. As mentioned, specific studies in children are missing, with most of the current papers being focused on adults (often on the risks related to surgery for meningiomas) [ 24 , 25 , 26 ] or on the use of ASM prophylaxis [ 27 , 28 , 29 ]. The few studies on children usually comprise mixed series including either children with or without preoperative seizures.…”
Section: Discussionmentioning
confidence: 99%
“…52 53 Seizure is another common presenting symptom in 30% of meningioma patients, with surgical resection offering 60 to 90% seizure freedom with a 12 to 19% rate of de novo seizures. 54 Factors predicting preoperative seizures in meningioma patients are supratentorial (non-skull base) tumor location (mostly convexity and parasagittal) and perilesional edema on imaging. Tumor grading is another strong predictor; WHO grades 2 and 3 had a preoperative seizure occurrence of 31% compared to 15% of noninvasive meningiomas (WHO grade 1).…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Tumor grading is another strong predictor; WHO grades 2 and 3 had a preoperative seizure occurrence of 31% compared to 15% of noninvasive meningiomas (WHO grade 1). 54,55 Patients with parasagittal and brain convexity meningiomas can present with paresis or paralysis of the affected contralateral limb. Patients with sphenoid ridge meningiomas with the involvement of the supraorbital fissure or the cavernous sinus can present with cranial nerve palsies and seizures.…”
Section: Clinical Presentationmentioning
confidence: 99%